ҚАРАҚАЛПАҚ ТИЛИНДЕ СОМАТИКАЛЫҚ ЛИНГВОМӘДЕНИЙ КОДЫНЫҢ ФРАЗЕОЛОГИЗМЛЕР ҚУРАМЫНДА БИЛДИРИЛИЎИ - Шынназарова, Саодат Жубаткановна (ILIM hám JÁMIYET, 2026)
This article discusses the concept of code in linguoculturology, its essence, specific features, and types. In particular, it substantiates the role of code in explaining the national and cultural characteristics of the Karakalpak language and presents scholarly views and reflections on the somatic linguocultural code. Through illustrative examples, it is demonstrated that in the lexicon of the Karakalpak language, the somatic code functions as a core component of a number of lexemes and linguistic units.